Comparative studies between HTLV-1 and HTLV-2 function and pathobiology - Francoise Bex (Frontiers Research Topics, 2015)
Human T-cell leukemia viruses type 1 and 2 (HTLV-1 and HTLV-2) share a common genetic organization, expression strategy and ability to infect and immortalize T-cells in vitro; however, HTLV-1 and HTLV-2 are strikingly different in terms of clinical impact. HTLV-1 is recognized as the aetiological agent of adult T-cell leukemia/lymphoma (ATLL), and HTLV-associated myeolopathy/tropical spastic paraparesis (HAM/TSP), in contrast, HTLV-2 does not cause hematologic disorders and is only sporadically associated with cases of subacute myelopathy. HTLV-1 and HTLV-2 also exhibit distinct cellular tropisms in vivo: HTLV-1 is mainly found in CD4+T lymphocytes, whereas CD8+T-cells are the preferred target for HTLV-2. The articles contributed in this Research Topic are covering all the different aspects that characterize HTLV-1 and HTLV-2, by highlighting differences in their biology that might provide clues to their distinct pathogenic properties.